Effect of Subcision and Microneedling in the Treatment of Atrophic Acne Scars in Ten Patients: A Case Series - Tulika Rai; Megha Tandon (Nepal Journal of Dermatology, Venereology & Leprology)
Background: Acne vulgaris is a common condition with a prevalence of over 90% among adolescents and post- acne scarring is a well known sequelae. Different types of scars (ice pick, boxcar, and rolling scars) warrant a customized approach of treatment for each type. We propose a novel treatment of atrophic acne scars using combination of subcision and microneedling.